2020
DOI: 10.1080/13670050.2020.1718592
|View full text |Cite
|
Sign up to set email alerts
|

A showdown between bilingual and mainstream education: the impact of language of instruction on learning subject content knowledge

Abstract: Bilingual education has become popular in many countries in the last two decades. It is generally acknowledged that learning a second language (L2) through subject content has a positive impact on students' L2 learning, but there is less agreement on whether this also applies to learning subject content knowledge in and through L2. This cross-sectional study compared Dutch pre-university mainstream and bilingual education students in grades 7 and 9 on a history knowledge test, taking into consideration the lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Extensive research in CLIL has found that it has language-related benefits for students without significantly affecting the acquisition of content knowledge (Pérez-Cañado, 2012). In one case, students in a CLIL history context required additional class time to make content gains similar to their peers (Dallinger et al, 2016), but in another case they outperformed their non-CLIL peers in terms of content knowledge (Oattes et al, 2020).…”
Section: Teaching Written Historical Contextualization In L1/l2 Settingsmentioning
confidence: 99%
“…Extensive research in CLIL has found that it has language-related benefits for students without significantly affecting the acquisition of content knowledge (Pérez-Cañado, 2012). In one case, students in a CLIL history context required additional class time to make content gains similar to their peers (Dallinger et al, 2016), but in another case they outperformed their non-CLIL peers in terms of content knowledge (Oattes et al, 2020).…”
Section: Teaching Written Historical Contextualization In L1/l2 Settingsmentioning
confidence: 99%